Hotel Portofino - O'Connell, J. P. (Blackstone Publishing, 2022)
A heady historical drama about a British family who opens an upper-class hotel on the magical Italian Riviera during the Roaring Twenties. Hotel Portofino has been opne for only a few weeks, but already the problems are mounting for its owner Bella Ainsworth. Her high-class guests are demanding and heard to plase. And she's being targeted by a scheming and corrupt local politican, who threatens to drag her into the red-hot cauldron of Mussolini's Italy. To make matters worse, her marriage is in trouble, and her children are still struggling to recover from the repercussions of the Great War. All eyes are on the arrival of a potential love match for her son Lucian, but events don't go to plan, which will have far-reaching consequences for the whole family. Set in the breathtakingly beautiful Italian Riviera, Hotel Portofino is a story of personal awakening at a time of global upheaval and of the liberating influence of Italy's enchanting culture, climate, and cuisine on British "innocents abroad." --